Inflammatory response of endothelial cells to hepatitis C virus recombinant envelope glycoprotein 2 protein exposure - Urbaczek, Ana Carolina; Ribeiro, Lívia Carolina De Abreu; Ximenes, Valdecir Farias [UNESP]; Afonso, Ana; Nogueira, Camila Tita; Generoso, Wesley Cardoso; Alberice, Juliana Vieira; Rudnicki, Martina; Ferrer, Renila; Fonseca, Luiz Marcos Da; Costa, Paulo Inácio Da (Instituto Oswaldo Cruz, Ministério da Saúde, 2014)
The hepatitis C virus (HCV) encodes approximately 10 different structural and non-structural proteins, including the envelope glycoprotein 2 (E2). HCV proteins, especially the envelope proteins, bind to cell receptors and can damage tissues. Endothelial inflammation is the most important determinant of fibrosis progression and, consequently, cirrhosis. The aim of this study was to evaluate and compare the inflammatory response of endothelial cells to two recombinant forms of the HCV E2 protein produced in different expression systems (Escherichia coli and Pichia pastoris). We observed the induction of cell death and the production of nitric oxide, hydrogen peroxide, interleukin-8 and vascular endothelial growth factor A in human umbilical vein endothelial cells (HUVECs) stimulated by the two recombinant E2 proteins. The E2-induced apoptosis of HUVECs was confirmed using the molecular marker PARP. The apoptosis rescue observed when the antioxidant N-acetylcysteine was used suggests that reactive oxygen species are involved in E2-induced apoptosis. We propose that these proteins are involved in the chronic inflammation caused by HCV.
Keywords: HCV -; E2 protein -; inflammation -; HUVEC